The effect of Starbucks Marketing Campaigns on Consumer Buying Behaviour - Nair, Rajesh Kumar; Sinha, Rupesh; Crasto, Sheryl George; Kian, Khor Wee; Kee, Daisy Mui Hung; Binti Abdullah, Shamin Athirah; Zaidi, Siti Nuraliah Ninti; En, Tan Shiaw; Jain, Arun Kumar; Valecha, Pallavi M; Ganatra, Varsha (Asia Pacific Journal of Management and Education (APJME), 2021)
Starbucks is the global coffee and snack brand which is headquartered in America. Starbucks is a disciplined innovator, and good management of its innovation timeline is one of the primary reasons behind the company’s success. This is also the main reason why Starbucks has been able to improve its store sales. Excellent employee training management and excellent service attitude also attracted a lot of customers and improved customer satisfaction effectively. Over the years, Starbucks has adopted various innovative marketing campaigns globally to attract its potential customers, increasing the sales and impacting the customer buying behaviour. The aim of this research is to understand the effect and impact of Starbucks Marketing campaigns through various channels on its customers. The research will be conducted across the regions of India and Malaysia through survey and observational method.